Geological History of Southeastern Gorgonum Chaos, Mars: A Story of Water and Wind. Issue 9 (10th September 2021) - Haack, David; Adeli, Solmaz; Hauber, Ernst
Abstract: Gorgonum Chaos is part of the Eridania paleolake in Terra Sirenum and displays a number of prominent light‐toned morphological features that bear a record of the regional climatic conditions throughout most of Martian history. Based on an intergrated analysis of orbital data, we mapped a 1, 500 km 2 area in the southeast of Gorgonum Chaos. Morphologic, spectroscopic, and stratigraphic analyses were used to determine age and composition of the main geological units in the area. We identified four major geological units with decreasing content of hydrated minerals from the oldest to the youngest units, which were completely free of hydrated minerals. In the study area, phyllosilicate‐rich Noachian units compose the majority of the basin floor. Deposits enriched with evaporites were formed around the Noachian/Hesperian transition and erosion created prominent inverted morphologies. Loess‐like material without significant amounts of hydrated minerals was deposited until the late Hesperian. The youngest unit is an Amazonian layer free of hydrated minerals that originated from volcanic activities. This succession of minerals reflects the transition from more humid climatic conditions with the ability to sustain liquid water on the planet's surface during the Noachian to the hyper‐arid Amazonian environment we observe currently on Mars. Plain Language Summary: Gorgonum Chaos is part of the Eridania basin, which is a former lake system located at the southern hemisphere of Mars. The landforms observed in this area and their variable brightness suggest dramatically changing climatic conditions during the history of Mars. In an area of 1, 500 km 2 in size, we analyzed different landforms, their spectral characteristics, and their temporal sequences to determine the age and composition of the geological units. We found four major geologic units whose content of hydrated minerals decreased dramatically from oldest to youngest. The oldest unit with a high content of clay minerals is about 3.7 billion years old and formed the former lake bottom. This is followed by a younger unit with a mineral composition that indicates desiccation of the lake and erosion by wind. These, in turn, were largely covered by materials deposited by wind, which show very little evidence of liquid water. The last and youngest unit is volcanic in origin and completely devoid of minerals indicative of water. This succession of minerals reflects the evolution of the Martian surface, which was capable to sustain liquid water in the early stages of the planet and lost this ability during a drastic climate change. Key Points: We produced a geological map of southeastern Gorgonum Chaos We find a succession from phyllosilicates to olivine in aeolian deposits The presence of water decreases over time